2012
DOI: 10.5301/hip.2012.9745
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of An Uncemented Hydroxyapatite Coated Hemiarthroplasty for Displaced Femoral Neck Fractures: A Clinical and Radiographic 2-Year Follow-Up Study

Abstract: The results suggest that an uncemented hydroxyapatite coated hemiarthroplasty can be used to treat displaced intracupsular femoral neck fractures with good clinical and radiographic outcomes at short term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Furthermore, previous studies [6, 9, 22] observed a distinctly low risk for CTHA-related complications. Although CTHA improves clinical outcomes, one safety concern is that interference with the cemented femoral component could promote the destabilisation of bone and cement components and thus increase the risk for complications, such as prosthetic loosening, prosthetic revision, periprosthetic fracture, dislocation, femur shaft fracture, hip pain, lower limb shortening and heterotopic ossification [10, 23]. This is of specific concern, as undergoing a THA has been considered a potential risk factor for morbidity and mortality [8, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies [6, 9, 22] observed a distinctly low risk for CTHA-related complications. Although CTHA improves clinical outcomes, one safety concern is that interference with the cemented femoral component could promote the destabilisation of bone and cement components and thus increase the risk for complications, such as prosthetic loosening, prosthetic revision, periprosthetic fracture, dislocation, femur shaft fracture, hip pain, lower limb shortening and heterotopic ossification [10, 23]. This is of specific concern, as undergoing a THA has been considered a potential risk factor for morbidity and mortality [8, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Modern uncemented implants are reported to have lower incidences of thigh pain. The Corail® stem (DePuy Synthes), when used in good bone stock, has been described as having as low as 0.6% (2/347) rate of unexplained thigh pain; however, in neck of femur surgery with osteoporotic bone, the rate may be as high as 31.9% [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study are in agreement with reports on the use of cementless hemiarthroplasty overall and for cementless fixation of stems for elective THA. 12,17,[20][21][22] Bezwada et al 17 compared the clinical outcomes of 248 patients (256 hips) with a mean age of 77 years (range, 65-95 years) who sustained displaced femoral neck fractures treated with cementless bipolar hemiarthroplasties. At a mean follow-up of 3.5 years (range, 3-5 years), the revision rate was 5% and the mean Harris Hip score improved to 82 points (range, 54-92 points).…”
Section: Discussionmentioning
confidence: 99%